Psycho‐Demographic Determinants of Young Consumers' Purchase Intention toward Counterfeit Apparel in a U.S. Counterfeit Capital. (10th May 2019) - Bakhshian, Sonia; Lee, Young‐A; Cao, Wei
Abstract : The purpose of this study was to examine the influence of six psychographic variables (materialism, novelty seeking, personal gratification, status consumption, value consciousness, and integrity) and three demographic variables (age, gender, and income) on attitude and purchase intention toward counterfeit apparel within the ports of Los Angeles and Long Beach. A paper‐based survey method was used with a convenience sample of college students at a large university in Los Angeles County. A total of 118 usable responses were obtained. Results of two separate sets of multiple regression analyses showed a significant and positive influence of attitude on purchase intention of counterfeit apparel. Value consciousness and integrity were negatively related to the purchase intention. Results also showed that men and people in the lower income range had more positive purchase intention toward counterfeit apparel. Implications for future research were also discussed.